Banana Republik & Co / Alifah Ilyana Mohd Rafi … [et al.] - Mohd Rafi, Alifah Ilyana; Laser, Jassinta; Mohd Fadzilla, Nur Syahira; Ramli, Nurul Akma An Najwa; Mohd Adaha, Siti Sarah (2022)
For assignment purposes, a case study is done on small business to provide greater exposure for students in entrepreneurship. Therefore, we did a case study on a small business, Banana Republik & Co. which is a family-owned business that was founded in early 2019 by Mr Amirul and Mrs Ashikin. We had followed all the procedures of the assignment and decided to hold an online interview through Google Meet with Mrs Ashikin to get some information about their business. We had set a date with Mrs Ashikin and interviewed her on the night of Friday, the 1st of April 2022. From the online interview, we had gathered a lot of information that is needed to complete the report on the case study. We have put together the information and constructed a business model canvas that consists of customer segments, value proposition, channel, customer relationships, revenue streams, key resources, key activities, key partners, and cost structure. Not only that, but we also get to know the current problems of Banana Republik & Co. in terms of lack of employees, rising market prices, high competition, inflexible operation time and pandemic situation. Hence, we have included some suggestions in the report for each of the problems, hoping that it will help Banana Republik & Co. to operate better in future.